2007
DOI: 10.1128/iai.00372-06
|View full text |Cite
|
Sign up to set email alerts
|

Yersiniabactin Is a Virulence Factor for Klebsiella pneumoniae during Pulmonary Infection

Abstract: Iron acquisition systems are essential for the in vivo growth of bacterial pathogens. Despite the epidemiological importance of Klebsiella pneumoniae, few experiments have examined the importance of siderophores in the pathogenesis of this species. A previously reported signature-tagged mutagenesis screen identified an attenuated strain that featured an insertional disruption in ybtQ, which encodes a transporter for the siderophore yersiniabactin. We used this finding as a starting point to evaluate the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
183
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(204 citation statements)
references
References 55 publications
12
183
1
2
Order By: Relevance
“…Iron acquisition is critical for bacteria to survive in blood or urinary tract, as these environments are iron deprived (Foxman et al, 2000). Knockout of ironacquisition genes has been shown to attenuate the virulence of many bacteria (Torres et al, 2001;Lawlor et al, 2007). Therefore, iron acquisition from the environment is essential for the pathogenesis of E. coli, and our results support this.…”
Section: Discussionsupporting
confidence: 79%
“…Iron acquisition is critical for bacteria to survive in blood or urinary tract, as these environments are iron deprived (Foxman et al, 2000). Knockout of ironacquisition genes has been shown to attenuate the virulence of many bacteria (Torres et al, 2001;Lawlor et al, 2007). Therefore, iron acquisition from the environment is essential for the pathogenesis of E. coli, and our results support this.…”
Section: Discussionsupporting
confidence: 79%
“…The proteins required for yersiniabactin synthesis are encoded by irp genes, and it is predicted that the transporters required for the secretion of this siderophore are encoded by the ybt and fyu genes, and the uptake receptor is encoded by ybtQ, although this remains to be thoroughly characterized in K. pneumoniae (319,321,330). Interestingly, yersiniabactin has been observed in only ϳ18% of classical but 90% of HV K. pneumoniae clinical isolates (319,329).…”
Section: Siderophoresmentioning
confidence: 99%
“…However, in conjunction with enterobactin, it is overrepresented in K. pneumoniae isolates from the respiratory tract (329). Notably, yersiniabactin is expressed during lung infection, and its activity is not inhibited by lipocalin-2 in vivo during early lung infection, likely because its structure significantly differs from that of enterobactin (311,321,329). This allows K. pneumoniae to grow to high bacterial loads in the lungs during infection (329).…”
Section: Siderophoresmentioning
confidence: 99%
“…Apart from plasmid-borne factors, genes encoding for ferric yersiniabactin uptake (fyuA) and iron-repressible protein (irp2) have been detected by PCR in more than 65% of strains isolated from cases of avian colibacillosis (Janssen et al, 2001). Subsequent work has shown that production of yersiniabactin contributes to virulence of exPEC and Klebsiella pneumoniae in mice (Schubert et al, 2002;Lawlor et al, 2007). Additionally, chuA (encoding a haeme utilization/transport protein) was detected by screening a signature-tagged mutagenesis bank of APEC O2 in chickens (Li et al, 2005), suggesting a role in virulence.…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%